2021
DOI: 10.1007/s00701-021-05034-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in mortality after intensive care of patients with traumatic brain injury in Finland from 2003 to 2019: a Finnish Intensive Care Consortium study

Abstract: Background Several studies have suggested no change in the outcome of patients with traumatic brain injury (TBI) treated in intensive care units (ICUs). This is mainly due to the shift in TBI epidemiology toward older and sicker patients. In Finland, the share of the population aged 65 years and over has increased the most in Europe during the last decade. We aimed to assess changes in 12-month and hospital mortality of patients with TBI treated in the ICU in Finland. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…This nding was also previously reported by the literature in both LMICs and HICs [25,[32][33]. Furthermore, GCS at admission, another widely used predictor of in-hospital mortality, [12,31,34], surprisingly, was not associated with outcome in this study. Most patients' scores in the GCS at hospital admission ranged between 3-5, and even though some individuals had higher GCS scores at emergency, as part of a severe TBI sample, at some point they evolved to loss of consciousness and lower scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This nding was also previously reported by the literature in both LMICs and HICs [25,[32][33]. Furthermore, GCS at admission, another widely used predictor of in-hospital mortality, [12,31,34], surprisingly, was not associated with outcome in this study. Most patients' scores in the GCS at hospital admission ranged between 3-5, and even though some individuals had higher GCS scores at emergency, as part of a severe TBI sample, at some point they evolved to loss of consciousness and lower scores.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the in-hospital mortality rate was 55%, signi cantly higher than the hospital mortality rates of 19.1-33.2% reported in other studies conducted in Brazil [5, 9-12], and even higher when compared to mortality rates in North America (13.3%), Europe (25.5%), and China 20.0% [23][24][25]. Interestingly, the mortality rate 1 year after discharge (15.1%) was lower than the mortality rate reported in other long-term studies in China (30%) [26], Europe (30%) [27] and India (44%) [6]. Therefore, the mortality rate is substantially high in the setting of this study, possibly explained by the severity of the injuries associated with limited diagnosis capabilities of intracranial injuries, delayed or inadequate initial care, lack of monitoring, and specialized treatment.…”
Section: Discussionmentioning
confidence: 73%
“…The authors focused on the most commonly reported patient's complaints and on abnormal physical examination findings–apart from evident external symptoms of head trauma and a low GCS score–that may raise suspicion of head trauma requiring urgent neurosurgical intervention. Our analysis revealed few interesting insights, a lot corresponds to the data from most European countries, where a shift in the age of head trauma patients from young patients to those >65 years old has been observed in recent years [ 10 ]. In contrast with a paper by Bossers et al [ 7 ], the most common cause of injuries in our study was falls on the same level.…”
Section: Discussionmentioning
confidence: 79%
“…In the current study, three PTA duration groups were assembled out of a cluster analysis distinguishing between different attention and EF capabilities at the initial stages of recovery rehabilitation. The additional three PTA duration groups suggested here are complementary to Russell’s scheme classification (Russell & Smith, 1961) becoming increasingly significant, as the number of patients who survive msTBI is increasing (Stein et al, (2010), especially among the younger patients (Luostarinen et al, 2022). Further research can use the PTA duration groups to evaluate the association of these markers with long-term cognitive outcomes (i.e., 1 year following pediatric TBI) and predict patterns of recovery.…”
Section: Discussionmentioning
confidence: 94%